2010
DOI: 10.1159/000319862
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Pruritus in Germany: Results of a Cross-Sectional Study in a Sample Working Population of 11,730

Abstract: Background: Pruritus is a frequent symptom in many diseases; its prevalence in German adults is unknown. Objective: Our purpose was to assess the prevalence, severity and health care of chronic pruritus in the German working population. Methods: A cross-sectional observational study was conducted in employees of 144 German companies. Pruritus-specific data were obtained by standardized questions. Results: 11,730 people (53.2% male, 16–70 years, mean = 43.7 years) were suitable for analysis. The point prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
118
2
16

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(155 citation statements)
references
References 32 publications
10
118
2
16
Order By: Relevance
“…However, this study did not differentiate between acute (AP) and chronic pruritus (CP, defined as pruritus lasting 6 weeks and longer [2,3]) and was also limited by the fact that it was conducted in a single city. More recent studies analysing the prevalence of CP in Germany have revealed an even higher prevalence than expected and showed a point prevalence of 13.5% in the general population (4) and 16.8% in working adults (5).…”
mentioning
confidence: 87%
“…However, this study did not differentiate between acute (AP) and chronic pruritus (CP, defined as pruritus lasting 6 weeks and longer [2,3]) and was also limited by the fact that it was conducted in a single city. More recent studies analysing the prevalence of CP in Germany have revealed an even higher prevalence than expected and showed a point prevalence of 13.5% in the general population (4) and 16.8% in working adults (5).…”
mentioning
confidence: 87%
“…The German study showed that prevalence increased with age from 12.3% (16∼30 years) to 20.3% (61∼70 years) 6 . According to a Turkish study with 4,099 elderly dermatological patients, 11.5% reported pruritus, whereas the highest prevalence was in patients older than 85 years 8 .…”
Section: Frequency Of Chronic Pruritusmentioning
confidence: 99%
“…In a German pilot study a life-time prevalence of 22.6% was surveyed 5 . A recent cross-sectional observational study in >11,000 employees of 144 German companies demonstrated a point prevalence of 17% among German employees 6 . A quarter of the affected persons had suffered from pruritus for more than 5 years.…”
Section: Frequency Of Chronic Pruritusmentioning
confidence: 99%
“…The prevalence of chronic pruritus lasting over 6 weeks is about 20 % in the general population [1][2][3]. Diagnostics include the clarification of possible causes, such as diabetes, renal, hepatic or hematologic diseases or infections.…”
Section: Indications For Magistral Formulas In Pruritusmentioning
confidence: 99%